PENGARUH KEPUASAN NASABAH DALAM PENGGUNAAN KARTU KREDIT PADA PT BANK UOB JAKARTA - Zahrina Lutfiana; Agus Sriyanto; Ismail, Habib (Sekolah Tinggi Ilmu Ekonomi Jayakarta, 2024)
The rapid development of technology is very influential on economic conditions in a country. Especially in the banking sector. The impact is a shift in people's behavior in consuming a good or service. The existence of this technological transformation must be addressed wisely, especially banks by innovating, efficiency and effectiveness of service services to customers. Banks need to improve Trust, Service Quality and Brand image in order to be competitive. This bank continues to strive to provide services in order to satisfy its customers. Bank UOB is a company engaged in banking that has its head office in Jakarta and branch offices in several other cities in Indonesia. The more advanced technological developments, many people are looking for an item or tool that is flexible, efficient and can be used whenever needed without having to waste so much time. In this era, banking increasingly refers to efforts to achieve social, economic progress, by making new products, providing better service quality and instilling trust and a good brand image in customers.This study aims to prove and analyze the effect of trust, service quality, brand image on the satisfaction of Bank UOB Jakarta credit card users. The study population is all UOB Bank credit card users, sampling is carried out by probability sampling with the random sampling method, Data analysis using SPSS 23 the number of samples used was 70 respondents from 230 populations. The results proved that trust has a significant positive effect on UOB Bank credit card user satisfaction, service quality has a significant positive effect on UOB Bank credit card user satisfaction, brand image has a significant positive effect on UOB Bank credit card user satisfaction.